Accuracy Of Reporting On Online Media Public.Com Viral (Frame Analysis Model on Covid 19 News in Bengkulu) - Prasetyo, Wahyu Prasetyo wahyu; Asnawati, Asnawati; Narti, Sri (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
The purpose of this study was to find out about the accuracy of news "Press the Rate of Covid 19, Rohidin Encourages the Regions to Perform a Bulk SWAB Test", on 4 September  2020 at Viralpublik.com Bengkulu Online Media in operationalizing the four structural dimensions of news as a framing device: syntax, script, thematic and rhetorical on Covid 19 news. This research method is based on the postpositivism or interpretive philosophy that is used to examine the conditions of natural objects, where the researcher is the key instrument, and the results of qualitative research are to understand meaning, understand uniqueness, construct phenomena, and find hypotheses. In this method of analysis, the Zhongdang Pan and Gerald M. Kosick Model approach uses psychological and sociological conceptions on Covid 19 news. The results showed that the Covid 19 news about "Pressing the Rate of Covid, Rohidin Encourages the Regions to Perform a Mass SWAB Test, 4 September 2020", psychologically the conceptions have changed humans in communicating and interacting with others, because the framing concept used has described the selection process highlighting certain aspects of media reality in placing information in the context of news accuracy, so that certain news content gets a greater allocation than other news issues, whereas in a sociological concept, it can be understood as the process of how a person classifies, organizes, and interprets his social experience to understand himself and the reality outside himself, because a pandemic can cause changes in behavior that have an impact on social upheaval in society